Integrated testing system of information competence components of future translators - Rostyslav O. Tarasenko; Svitlana M. Amelina; Albert A. Azaryan (Academy of Cognitive and Natural Sciences, 2020)
The article deals with the diagnosis of the formation of the information competence components of translators through testing. The use of testing to determine the level of formation of the information-thematic component of the information competence of translators is demonstrated. It has been established that one of the ways to form the information-thematic component of information competence in the aspect of studying terminology can be the use of thematic networks. The development of a thematic network is shown on the example of the thematic network "Electrical equipment". The stages of test control, which are consistent with the logic of the organization of the educational process and the process of forming the information competence of the future translator according to the scheme of the developed thematic network, have been determined. These stages are the current, thematic, modular, final testing. The main types of test tasks are defined, the combination of which allows diagnosing the level of formation of the information-thematic component of students' information competence. Criteria and principles for the selection of test tasks for each of the testing stages are proposed. The ratio of test tasks of different types and complexity at the determined testing stages has been developed. The results of an experimental study on the diagnosis of the formation of the informationthematic component of the information competence of future translators by applying the developed integrative testing system using the Moodle platform are presented.